2020
DOI: 10.3390/biomedicines8120633
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD146 (MCAM) in Physiological and Pathological Angiogenesis—Contribution of New Antibodies for Therapy

Abstract: The fundamental role of cell adhesion molecules in mediating various biological processes as angiogenesis has been well-documented. CD146, an adhesion molecule of the immunoglobulin superfamily, and its soluble form, constitute major players in both physiological and pathological angiogenesis. A growing body of evidence shows soluble CD146 to be significantly elevated in the serum or interstitial fluid of patients with pathologies related to deregulated angiogenesis, as autoimmune diseases, obstetric and ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 98 publications
0
32
0
Order By: Relevance
“…These results are supported by our study, with pathway analysis of DE serum miRNAs predicting upstream regulation by TGF-β signalling. In other tissues, TGF-β is involved in the regulation of angiogenesis in wound healing, along with CD146, laminins and other basement-membrane-associated proteins [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by our study, with pathway analysis of DE serum miRNAs predicting upstream regulation by TGF-β signalling. In other tissues, TGF-β is involved in the regulation of angiogenesis in wound healing, along with CD146, laminins and other basement-membrane-associated proteins [ 78 , 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of previous studies have demonstrated that CD146 is not only an adhesion molecule, but also a cellular surface receptor stimulated by miscellaneous ligands, including extracellular matrices and growth factors ( 36 , 37 ). By binding to its corresponding ligands, CD146 closely participates in a number of cell processes, such as proliferation, migration ( 38 ), hypertrophy ( 39 ), angiogenesis ( 40 ) and apoptosis ( 40 , 41 ). CD146 is mostly involved in the development and injury of organs, and the progression of various cancer types to metastases, such as oral cancer, ovarian carcinoma, hepatocellular carcinoma and acute lymphocytic leukemia ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blot-Chabaud and his group identified, in addition to the membrane-anchored form of CD146, a soluble form (sCD146) [20,35,[72][73][74] that is mainly generated by the proteolytic cleavage of the membrane form through metalloproteases [19,35]. As already re- The molecular heterogeneity of the two subpopulations at different stages of melanoma disease and during follow-up also was evident for the floating genes.…”
Section: Soluble Cd146 Form In Melanoma Patientsmentioning
confidence: 91%
“…The lgCD146 displays two phosphoryla protein kinase (PKC) and double leucine motifs for baso-lateral membra while the shCD146 isoform contains one PKC and one PDZ-binding domai an involvement in cell signaling [17,18]. In endothelial cells, lgCD146 is dist cell junction and is involved in structural functions, while shCD146 is expres apical pole, contributing to the angiogenetic process [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%